2021 14th IEEE Conference on Software Testing, Verification and Validation (ICST) 2021
DOI: 10.1109/icst49551.2021.00050
|View full text |Cite
|
Sign up to set email alerts
|

Digital Twins Are Not Monozygotic – Cross-Replicating ADAS Testing in Two Industry-Grade Automotive Simulators

Abstract: This is a repository copy of Digital Twins Are Not Monozygotic -cross-replicating ADAS testing in two industry-grade automotive simulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…As previously mentioned, digital twins have supported several testing activities, at the different X-in-the-Loop test level, including test generation [4,5,6] or anomalies detection [9]. Our hypothesis has as presumes that multi-fidelity digital twins can support on significantly enhancing several test, verification and validation activities (e.g., test generation, test oracle generation, debugging) that are not supported with common digital twins.…”
Section: Multi-fidelity Digital Twinsmentioning
confidence: 89%
See 2 more Smart Citations
“…As previously mentioned, digital twins have supported several testing activities, at the different X-in-the-Loop test level, including test generation [4,5,6] or anomalies detection [9]. Our hypothesis has as presumes that multi-fidelity digital twins can support on significantly enhancing several test, verification and validation activities (e.g., test generation, test oracle generation, debugging) that are not supported with common digital twins.…”
Section: Multi-fidelity Digital Twinsmentioning
confidence: 89%
“…Furthermore, digital twins highly rely on their simulation environment (e.g., Simulink) and solver-specific configurations. For instance, a recent study showed that the same digital twin can produce different results for the same test scenario when being executed in two different environments [4]. In a similar line, if the digital twin is to be used locally, in parallel with the real execution of the CPS, this shall not be a high priority task in order not to interfere safety-critical functionalities.…”
Section: Multi-fidelity Digital Twinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current study responds to this call, and motivates our work on systems testing in simulated environments. With regard to a different perspective, Borg et al [50] discuss the consistency between the test results obtained from running the same experiments based on two different simulators and investigate the reproducibility of the results in both simulators. When running the same testing campaign in PreScan and ESI Pro-SiVIC, the authors found notable differences in the test outputs related to revealed safety violations and the dynamics of cars and pedestrians.…”
Section: Related Workmentioning
confidence: 99%
“…In [24] a comparison between testing of DNN-based ADAS using real-world and simulator-generated data is conducted and it is also showed that how on-line and off-line testing of these systems can differ and meanwhile complement each other. Markus et al studied the consistency between the results obtained from two different simulators and investigated whether the obtained results could be mutually reproducible in both simulators [13].…”
Section: Related Workmentioning
confidence: 99%